In vitro clonal propagation of BARI Ada-1 (Zingiber officinale Rosc.) (Jahangirnagar University Journal of Biological Sciences, 2016)
Abstract not availableJahangirnagar University J. Biol. Sci. 4(2): 53-57, 2015 (December)